Epicardial radiofrequency catheter ablation of Brugada syndrome with electrical storm during ventricular fibrillation: A case report. Issue 46 (November 2017) - Jiang, Shufen; Yin, Xiaomeng; Dong, Chang; Xia, Yunlong; Liu, Jinqiu
Abstract: Rationale: Brugada syndrome (BrS) is characterized by ST segment elevation at the J point ≥2 mm in the right precordial electrocardiogram (ECG) leads, in the absence of structural heart disease, electrolyte disturbances, or ischemia. It is a well-described cause of sudden death in young patients, especially in the age of between 30 and 40 years old. Here, we reported an unusual case of electrical storm (ES) of ventricular fibrillation (VF) caused by BrS with complete right bundle-branch block (CRBBB) in a 75-year-old male patient. Patient concerns: A 75-year-old male patient survived sudden cardiac death caused by a ventricular ES. He presented with the cove-shaped ST elevation of 2 mm in lead V1 with typical CRBBB and lacked structural cardiomyopathy and coronary heart disease. The patient suffered ventricular ES again, although the implantable cardioverter defibrillator(ICD) had implanted. Diagnoses: Brugada syndrome with complete right bundle-branch block. Interventions: Implantable cardioverter defibrillator (ICD) implantation was performed. But this therapy could not prevent the recurrence of malignant arrhythmia. Finally, the ES was treated successfully using radiofrequency catheter ablation (RFCA) at the area of the free wall of the right ventricular outflow tract (RVOT) epicardium. Outcomes: During 7 months of follow-up, the patient was asymptomatic and free of arrhythmic events. Lessons: As far as we know, the patient is the oldest patient reported to have BrS. RFCA offers an alternative therapy for patients with BrS, especially when ICD shocks are encountered.